Managing hyperglycaemia during antenatal steroid administration, labour and birth in pregnant women with diabetes – an updated guideline from the Joint British Diabetes Society for Inpatient Care. Issue 2 (7th December 2021) - Dashora, Umesh; Levy, Nicholas; Dhatariya, Ketan; Willer, Nina; Castro, Erwin; Murphy, Helen R.; ,
Abstract: This article summarises the Joint British Diabetes Societies for Inpatient Care guidelines on the management of glycaemia in pregnant women with diabetes on obstetric wards and delivery units, Joint British Diabetes Societies (JBDS) for Inpatient Care Group, ABCD (Diabetes Care) Ltd. The updated guideline offers two approaches – the traditional approach with tight glycaemic targets (4.0–7.0 mmol/L) and an updated pragmatic approach (5.0–8.0 mmol/L) to reduce the risk of maternal hypoglycaemia whilst maintaining safe glycaemia. This is particularly relevant for women with type 1 diabetes who are increasingly using Continuous Glucose Monitoring (CGM) and Continuous Subcutaneous Insulin Infusion (CSII) during pregnancy. All women with diabetes should have a documented delivery plan agreed during antenatal clinic appointments. Hyperglycaemia following steroid administration can be managed either by increasing basal and prandial insulin doses, typically by 50% to 80%, or by adding a variable rate of intravenous insulin infusion (VRIII). Glucose levels, either capillary blood glucose or CGM glucose levels, should be measured at least hourly from the onset of established labour, artificial rupture of membranes or admission for elective caesarean section. If intrapartum glucose levels are higher than 7.0 or 8.0 mmol/L on two consecutive occasions, VRIII is recommended. Hourly capillary blood glucose rather than CGM glucose measurements should be used to adjust VRIII. The recommended substrate fluid to be administered alongside a VRIII is 0.9% sodium chloride solution with 5% glucose and 0.15% potassium chloride (KCl) (20 mmol/L) or 0.3% KCl (40 mmol/L) at 50 ml/hr. Both the VRIII and CSII rates should be reduced by at least 50% after delivery.